Single-faceted IrO2 monolayer enabling high-performing proton exchange membrane water electrolysis beyond 10,000 h stability at 1.5 A cm-2 - Deren Yang; Chunyang Zhang; Yufeng Qin; Yang Yue; Yubo Liu; Xiaoyun Shi; Kang Hua; Xuemin An; Louyu Jin; Yipeng Zhang; Shouwei Zuo; Aidong Tan; et al. (Nature Communications)
Abstract Both commercial and laboratory-synthesized IrO2 catalysts typically possess rutile-type structures with multiple facets. Theoretical results predict the (101) facet is the most energetically favorable for oxygen evolution reaction owing to its lowest energy barrier. Achieving monolayer thickness while exposing this desired facet is a significant opportunity for IrO2. Herein, we develop an ammonia-induced facet engineering for the synthesis of single-faceted IrO2(101) monolayer. It achieves 230 mV overpotential at 10 mA cmgeo -2 in a three-electrode system and 1.70 V at 2 A cmgeo -2 in a proton exchange membrane (PEM) electrolyzer. Though facet engineering primarily contributes to modulating the intrinsic activity rather than stability, single-faceted IrO2 monolayer performs over 10,000-hour stability at constant 1.5 A cmgeo -2 (3.95 mV kh-1 decay) and 1000-hour stability at 0.2 mgIr cmgeo -2 under fluctuating conditions. This work proposes that ammonia-induced facet engineering of IrO2 monolayer enables facet-dependent oxygen evolution reaction (OER) performance and high stability in industrial-scale PEM electrolysis.